Optimering av bränslemix vid avfallsvärmeverk : genom tillsats av gummidäck - Ljungkvist, Niklas (2013)
BDX has 40 years of experience of recycling and reprocessing by-product and residues at SSAB (Swedish Steel AB) in Luleå. BDX would like to find other areas of the waste industry where their knowledge is useful and where BDX can develop new solutions. Finding new ways to reuse waste tires is one of those, both in terms of material reuse and energy recovery. The goal of this project has been to examine how worn out tires can be energy recovered within the geographical region and if it is economically feasible to optimize and improve the current fuel mix in waste fuel boilers by adding rubber from worn out tires.Initially, the waste market and its structure were investigated, what rules that are related to burning waste and what characteristics the current fuels have. A situation analysis of the collection and disposal of tires was carried out including how the existing waste facilities in Norrbotten and Västerbotten are operated and their attitude regarding burning tires. This was followed up by a technical analysis with index- and model calculations, to investigate if tires, with or without additional fuels, can have a positive influence on the boiler compared to only burning household and industrial waste from a combustion technical/chemical perspective. A tool for comparing the different mixtures during the index calculations was developed as well as ratios to analyze the model calculations. Finally the economical feasibility of the interesting mixtures was carried out to examine the possibility for BDX to enter this market of fuel delivery and treatment.The analysis of the index calculations compared to the model calculations shows that it is possible to analyze fuel mixes with the developed tool. However, the points for each mix does not correspond entirely to the results of the model calculations, this means that it should only be used to evaluate if the mix has a positive or negative effect compared to the reference mix.Today, there is no market in delivering a ready-to-burn fuel mix to the heating plants ...